External and Internal Barriers to Studying Can Affect Student Success and Retention in a Diverse Classroom - Laurence Clement (American Society for Microbiology, 2016)
Although a majority of under-represented minority (URM) students begin their postsecondary education at community colleges, little is known about barriers to success and retention for transfer-bound science students. This study focuses on some of the barriers that affect these students’ ability to study adequately for a community college “gateway” course. It tests whether instructors’ expectations of study time were realistic for community college students and whether students reported facing external barriers, such as job and family responsibilities, or internal barriers to studying, such as lack of motivational, cognitive, and metacognitive abilities, all of which have been shown to impact academic success and retention. It also tests whether students who faced such barriers were less likely to succeed in and complete the course, as well as whether time spent studying was related to course success. The findings reported here show that community college students do not have enough available time to study and that external and internal barriers are both prevalent among these students. In addition, students who faced such barriers are more likely to fail or drop the class. Results also show that study time is positively correlated with retention, but not performance, as well as with some motivational, cognitive, and metacognitive dimensions of self-regulated learning. These findings lead to new questions, including whether student success in a community college class is associated with the use of cognitive and metacognitive learning strategies for students with no prior degrees, and whether increased course structure may improve success for college students with lower self-regulated abilities.